Isolation and characterization of Bacteria in the ancient Javanese Pegon manuscript: “Layang Watu Gunung” - Rahmani, Tara Puri Ducha; Ahmad, Nur; Anasom, Anasom; Pertiwi, Salsabiela; Niam, Muhammad Yusrun; Kusuma, Hamdan Hadi; Watson, Lee James (Journal of Natural Sciences and Mathematics Research, 2023)
This research is one of the efforts and the first step in the preservation of historical ancient manuscripts with an interdisciplinary scientific approach. The Unity of Sciences involved in this research are historical science, archaeology, philology combined with natural sciences such as microbiology and biotechnology approaches. The ancient manuscript whose microorganisms were isolated and observed in this study is an ancient manuscript with Pegon letters titled "Layang Watu Gunung" which dates from the 19th century. Over time, microorganisms can contaminate the paper on the manuscript which can cause damage or biodeterioration. Efforts to preserve historical manuscripts can be started by identifying in advance what types of microorganisms are contaminating the manuscript. From the results of the study, it was found that the microorganisms that contaminate the Layang Watu Gunung Ancient Manuscript are types of bacteria and fungi. For bacteria, the results of the Gram staining test result for contaminant bacteria are Gram Negative Bacteria. This initial research will be the basis for further preservation efforts, the results will be more relevant to be analyzed, especially for other historical manuscripts that are in similar temperature and humidity conditions, namely on the island of Java.